PERFORMANCE LOSSES CAUSED BY WHITE FLIES IN YUCCA CULTIVATION - VARGAS-H., OCTAVIO; BELLOTTI, ANTHONY C. (Revista Colombiana de Entomología, 1981)
Whiteflies population (Aleurotrachelus socialis, Bemisia tuberculata, Traileurodes variabais) causes leaf yellowing deformation of the growing plants and a sooty mold which grows in the sugar excretion of the insect. In the Espinal (Tolima) area where whiteflies populations are high throughout the year several varieties have been tested for resistance and economic damage. The treated plants presented lower grades of infestation and higher yields, compared with the untreated ones. Yield losses due to whiteflies depend on the variety. Lines % yield loss H 305 - 122 79.6 CMC 57 76.7 VEN 218 68.0 CMC 40 52.0 N MEX 59 33.6 The yield depression depends on the duration of the attack, presenting a significant negative correlation (r = 0.90). The yield loss of 79.6% in the hybrid 305 - 122 would represent a loss of 97.350. If farmers apply insecticides every 3 months the root yield production would be higher. Even though chemical control has been effective in preventing or reducing the damage caused by whiteflies, it is generally agreed that the most efficient method of control would be to develop material that is resistant to whiteflies.